The Brigham intensive review of internal medicine - Singh, Ajay, 1960-; Loscalzo, Joseph; Brigham and Women's Hospital ([New York] : Oxford University Press, 2014)
Based upon the popular review course from Harvard Medical School, the'Brigham Intensive Review of Internal Medicine' is a comprehensive study guide for the American Board of Internal Medicine certification or maintenance of certification examination as well as for general practice review by physicians and residents.
This edition previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 27, 2016).
Keywords: Internal medicine